ANALYSIS OF OLDER WORKERS ABILITY IN USING INFORMATION TECHNOLOGY AT DINAS PANGAN DAERAH SULUT IN INCREASING WORK PERFORMANCE - Rudolf Jonatan Polii; Willem J. F. A. Tumbuan; Regina T. Saerang (Universitas Sam Ratulangi, 2023)
The purpose of this study is to examine the daily experience of the ability in using information technology (IT) by older workers at Dinas Pangan Daerah Sulut, to identify the factors that affect the ability of older workers in the usage of IT at Dinas Pangan Daerah Sulut, and also to identify ways in which Dinas Pangan Daerah Sulut needs to implement strategies that will contribute to work performance and overall effectiveness for older workers in using and developing Information Technology. This study uses a qualitative approach with data collection using interviews with 10 civil servants at Dinas Pangan Daerah Sulut who are over 50 years old or classified as older workers. Results found that daily experience of older workers’ ability in using information technology still has difficulties in using software that has a high complexity of use. On the positive side, information technology is a tool that can help them increase their work performance. The ability in using IT of older workers IT influenced by age, intention, educational background, and also financial factors that support IT facilities for older workers. Older workers need good management innovations such as direct and indirect training as well as good work synergy between generations in the workplace. Keywords: Older Workers, Work Ability, Information Technology, Work Performance